2020
DOI: 10.18415/ijmmu.v7i11.2149
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Mathematical Reasoning Ability Viewed from Personality Type Rational and Idealist

Abstract: This finds out about pursuits to (1) describe the mathematical reasoning ability of high school students as viewed from the rational and idealist personality types; (2) knowing the causes of students' errors in answering questions. This type of research is qualitative research. The subjects of this research were eleventh-grade students of high school 1 Wanasaba East Lombok. Determination of the concern using purposive sampling. Data collection methods used personality tests and mathematical reasoning exams on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The adaptation process takes time and can have an impact on these abilities. In addition, the 2015 Trend In International Mathematics And Science Study (TIMSS) data shows that the mathematical ability of Indonesian students is ranked 44th out of 49 countries (Akrom & Triyanto, 2021). Meanwhile, the results of the 2018 PISA study released by the OECD in 2019 showed that the mathematical reasoning ability of Indonesian students was ranked 72 out of 78 countries (Nurjanah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation process takes time and can have an impact on these abilities. In addition, the 2015 Trend In International Mathematics And Science Study (TIMSS) data shows that the mathematical ability of Indonesian students is ranked 44th out of 49 countries (Akrom & Triyanto, 2021). Meanwhile, the results of the 2018 PISA study released by the OECD in 2019 showed that the mathematical reasoning ability of Indonesian students was ranked 72 out of 78 countries (Nurjanah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%